Should Pediatric Endocrinologists Consider More Carefully When to Perform a Stimulation Test? - Penco, Arturo; Bossini, Benedetta; Giangreco, Manuela; Vidonis, Viviana; Vittori, Giada; Grassi, Nicoletta; Pellegrin, Maria Chiara; Faleschini, Elena; Barbi, Egidio; Tornese, Gianluca (Frontiers in Endocrinology, 2021)
Introduction: Pediatric endocrinology rely greatly on hormone stimulation tests which demand time, money and effort. The knowledge of the pattern of pediatric endocrinology stimulation tests is therefore crucial to optimize resources and guide public health interventions. Aim of the study was to investigate the distribution of endocrine stimulation tests and the prevalence of pathological findings over a year and to explore whether single basal hormone concentrations could have saved unnecessary stimulation tests. Methods: Retrospective study with data collection for pediatric endocrine stimulation tests performed in 2019 in a tertiary center. Results: Overall, 278 tests were performed on 206 patients. The most performed test was arginine tolerance test (34%), followed by LHRH test (24%) and standard dose Synachten test (19%), while the higher rate of pathological response was found in insulin tolerance test to detect growth hormone deficiency (81%), LHRH test to detect central precocious puberty (50%) and arginine tolerance test (41%). No cases of non classical-congenital adrenal hyperplasia were diagnosed. While 29% of growth hormone deficient children who performed an insulin tolerance test had a pathological peak cortisol, none of them had central adrenal insufficiency confirmed at low dose Synacthen test. The use of basal hormone determinations could save up to 88% of standard dose Synachten tests, 82% of arginine tolerance + GHRH test, 61% of LHRH test, 12% of tests for adrenal secretion. Conclusion: The use of single basal hormone concentrations could spare up to half of the tests, saving from 32,000 to 79,000 euros in 1 year. Apart from basal cortisol level <108 nmol/L to detect adrenal insufficiency and IGF-1 <-1.5 SDS to detect growth hormone deficiency, all the other cut-off for basal hormone determinations were found valid in order to spare unnecessary stimulation tests.